Inclusion Complexes of Concentrated Orange Oils and β-Cyclodextrin: Physicochemical and Biological Characterizations - Torres Álvarez, Cynthia; Castillo, Sandra; Sánchez García, Eduardo; Aguilera González, Carlos Javier; Galindo Rodríguez, Sergio Arturo; Gabaldón Hernández, José A.; Báez González, Juan Gabriel (Molecular Diversity Preservation International, 2020)
Concentrated orange oils (5x, 10x, 20x) are ingredients used in different industries as components of flavors and aromas due to their great organoleptic qualities. This research focuses on the search for alternative uses for their application through encapsulation in inclusion complexes with β-cyclodextrin (β-CD). Inclusion complexes of concentrated orange oils (COEO) and β-CD were developed by the co-precipitated method in ratios of 4:96, 12:88, and 16:84 (w/w, COEO: β-CD). The best powder recovery was in the ratio 16:84 for the three oils, with values between 82% and 84.8%. The 20x oil in relation 12:88 showed the highest entrapment efficiency (89.5%) with 102.3 mg/g of β-CD. The FT-IR analysis may suggest an interaction between the oil and the β-CD. The best antioxidant activity was observed in the ratio 12:88 for the three oils. The antifungal activity was determined for all the inclusion complexes, and the 10x fraction showed the highest inhibition at a concentration of 10 mg/mL in ratios 12:88 and 16:84. Antibacterial activity was determined by the minimum inhibitory concentration (MIC) and was found at a concentration of 1.25 mg/mL in ratios 12:88 and 16:84 for 5x and 20x oils.